Open Textbooks Utilization by Undergraduate Library and Information Science Students in Delta State University, Nigeria - Iroroeavwo Achugbue, Edwin; Kolawole Ogunbodede, Francis (Ghana Library Journal, 2025)
The study examined open textbooks utilization by undergraduate Library and Information Science students at Delta State University, Abraka, Nigeria. The study’s population consisted of 447 students. The sample size of 220 was adapted using the Taro Yamane sampling technique. The instrument used to collect data was the questionnaire. The validity of the instrument was determined using Cronbach’s Alpha and got 0.79. The quantitative data were analyzed using SPSS version 29. The study reveals that LIS undergraduate students have a high level of awareness and usage of open textbooks. The Diffusion of Innovations theory confirms the role of awareness as an important stage in innovation adoption (open textbooks). The study found a substantial association between LIS undergraduate students’ awareness and utilization of open textbooks. With increasing awareness, students are likely to conduct more research and use open textbooks. Based on the findings, it was suggested that the university management and instructors from LIS should develop sustained efforts towards promoting open textbooks among students. Attempts should also be made to improve the campaigns so that students are aware of the availability and advantages of open textbooks. Working with publishers and stakeholders in implementing open textbooks adoption into other departments or academic programs is also recommended.